Pollen record and integrated high-resolution chronology of the early Pliocene Dacic Basin (southwestern Romania) - Popescu, Speranta-Maria; Krijgsman, Wout; Suc, Jean-Pierre; Clauzon, Georges; Mărunţeanu, Mariana; Nica, Toma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2006)
International audience An integrated stratigraphic study has been performed on four early Pliocene fssections in the western Dacic Basin, including the long reference section of Lupoaia. Based on the integration of Mediterranean nannoplankton assemblages, the regional lignite stratigraphy, records of large and small mammals, large climatic fluctuations according to pollen grains, and climatostratigraphic relationships at the European scale, it has been possible to establish a magnetostratigraphic correlation of the different sections to the Geomagnetic Polarity Time Scale (GPTS). This correlation suggests that all normal episodes of the early Pliocene (from Thvera to Cochiti chrons) are recorded. Hence, the complete pollen record covers an almost continuous time span from about 5.33 to 4.30 Ma. In addition, the regional Dacian/Romanian stage boundary in the Dacic Basin is located in the Nunivak (C3n.3n) episode with an age of 4.55±0.05 Ma. Our chronologic calibration, combined with high-resolution pollen data, results in a detailed record of paleoclimate in which the ~100 kyrs and ~400 kyrs eccentricity cycles are clearly identified.